British Medical Association family doctor guide to indigestion and ulcers - Hawkey, C. J. (Dorling Kindersley LondonGB, 2000)
Explains how the digestive system works; and also, the causes and symptoms of indigestion, heartburn and peptic ulcers. Provides self-help strategies e.g. lifestyle and diet changes, for indigestion sufferers. Identifies symptoms which may indicate cancer of the stomach, and therefore require immediate medical attention.